2010
DOI: 10.1093/ejo/cjq052
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the outcome of orthodontic treatment of Class III malocclusions--a systematic review

Abstract: The purpose of this study was to systematically review the orthodontic literature to assess the effectiveness of a prediction of outcome of orthodontic treatment in subjects with a Class III malocclusion. A structured search of electronic databases, as well as hand searching, retrieved 232 publications concerning the topic. Following application of inclusion and exclusion criteria, 14 studies remained. Among other data, sample ethnicity, treatment method, age at the start and completion of treatment, age at fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 14 publications
3
27
0
3
Order By: Relevance
“…However, the parameters that were used across these studies varied widely. Some of them have been analyzed in a review by Fudalej et al [10], who evaluated 14 studies for predictors and identified 38 variables. Most authors used combinations of three or four parameters for prognosis, gonial angle and Wits appraisal being the most common, followed by mandibular length and the SNA, SNB, and ANB angles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the parameters that were used across these studies varied widely. Some of them have been analyzed in a review by Fudalej et al [10], who evaluated 14 studies for predictors and identified 38 variables. Most authors used combinations of three or four parameters for prognosis, gonial angle and Wits appraisal being the most common, followed by mandibular length and the SNA, SNB, and ANB angles.…”
Section: Introductionmentioning
confidence: 99%
“…However, a noteworthy difference in terms of prediction models has been reported in the previous studies 11 with no evidence of prognostic agreement among the proposed models. Such a lack of evidence implies the choice of the prediction model to be empirical.…”
mentioning
confidence: 62%
“…However, agreement among prognostic models does not imply per se prognostic accuracy; it only implies that models yields to similar outcomes and, therefore, a given model may be preferred on the basis of easiness of landmark identification. In this regard, previous investigations 11,20 reported that stability of the orthopaedic treatment outcome of skeletal Class III malocclusion depends on several factors such treatment modality, timing, outcome evaluation, severity of malocclusion and individual patient responsiveness, making questionable the existence of a universal predictor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations